Improving international attractiveness of higher education institutions based on text mining and sentiment analysis - Santos, Carolina Leana (2022)
Santos, C. L., Rita, P., & Guerreiro, J. (2018). Improving international attractiveness of higher education institutions based on text mining and sentiment analysis. International Journal of Educational Management, 32(3), 431-447. DOI: 10.1108/IJEM-01-2017-0027